Biopolitics at 50 Years : Founding and Evolution - Wohlers, Tony; Fletcher, Amy (Research in biopolitics, 2023)
Biopolitics at 50 Years: Founding and Evolutionexplores the study of biology and politics through the prism of fifty years of experience presenting current research that illustrates the nature and evolution of biopolitics.